STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA YANG BERDAYA SAING DAN BERKELANJUTAN PADA AGROINDUSTRI TEBU: TINJAUAN LITERATUR DAN AGENDA PENELITIAN MENDATANG - Mursiti Mursiti; Illah Sailah; Marimin Marimin; Muhammad Romli; Alex Denni (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
The purpose of this paper was to analyze the sugarcane agroindustry situational, human resources, and regulations to obtain new research on sugarcane agroindustry. The method carried out was by collecting 50 articles from 2002 - 2020 from indexed journals, theses, books. Articles were divided into three parts, namely sugarcane agroindustry with 14 articles, human resources with 19 articles and 17 regulations. In the VUCA era, we need skills, systems thinking skills, predictive abilities, and the ability to change quickly which is coupled with the Covid-19 pandemic conditions that accelerate the need for digitalization in the VUCA era. The results of the analysis show that the problem of lagging human resources in Eastern Indonesia is caused by a mismatch between labour users' needs and the availability of skills. The non-oil and gas processing industry sector provide the largest contribution to employment, one of which is the sugarcane industry. The sugarcane agroindustry problem was the large gap between supply of 2.17 million tons and demand of 6.6 million tons of which the shortfall of 4.43 million tons is met through imports of raw crystal sugar. The government's efforts to suppress imports by encouraging the private sector to establish new sugar factories outside Java and the expansion of existing sugar factories are accompanied by the preparation of human resources, so that a strategy for developing human resources that is competitive and able to adapt to the environment is needed.Keywords: eastern Indonesia, human resources, situational analysis, sugar cane agro-industry, strategy